Ethnic inequalities in psychological distress among urban residents in the Netherlands: A moderating role of neighborhood ethnic diversity?. (July 2017) - Erdem, Özcan; Burdorf, Alex; Van Lenthe, Frank J.
Abstract: The main purpose of this study was to investigate whether neighborhood ethnic diversity moderated the association between ethnicity and psychological distress in the four largest cities of Netherlands. Multilevel linear regression analysis was used to assess whether the association between ethnicity and psychological distress differed by levels of neighborhood ethnic diversity. Results showed that the Turkish and Moroccan residents reported significantly higher psychological distress than native Dutch and Surinamese residents. In high ethnic diverse neighborhoods Turkish residents reported significantly less psychological distress than in low ethnic diverse neighborhoods. Ethnic diversity amplifies the risk of depression for some but not all ethnic minorities. Highlights: Studies have suggested that residing in a neighborhood with a high ethnic diversity was associated with more mental health problems. However, the moderating effect of neighborhood ethnic diversity on the association between individual-level ethnicity and mental health has been equivocal to date. Our study gives evidence that residing in high ethnic diversity neighborhoods is associated with better mental health in Turkish residents, but poorer mental health in other ethnic minorities. Ethnic diversity seems to have ethnic-specific effects on mental health.